Polycyclic aromatic hydrocarbons in volatile and particle phases over the vicinity of petrochemical refinery areas (hidrokarbon aromatik polisiklik dalam fasa meruap dan fasa zarah di persekitaran kawasan penapisan petrokimia) - Ramanathan, Sharanya; Mohd Jani, Siti Jariani; A. Ramly, Zamzam T; Huda, Muhammad Nurul; Lamia, Nowshin Jahan; Nawyal, Nazifa; Khan, Md Firoz (Penerbit Universiti Kebangsaan Malaysia, 2025)
The distribution of gaseous and particulate polycyclic aromatic hydrocarbons (PAHs), sources, and human exposure were studied around a petrochemical site located in Melaka, Malaysia from March 2021 - March 2022. Polyurethane (PUF) sampler devices were placed in six different areas to collect gaseous phase PAHs, and a High Volume Air Sampler (HVS) device was placed at a single location to collect PM2.5-bound PAHs. PUF samplers utilize porous foam to absorb PAHs passively with zero external power for long-term exposure monitoring. Meanwhile, the HVS device draws air at higher flow rates for more than a day. A total of sixteen PAHs were analyzed in both particulate and gaseous phases. The average concentrations for the gaseous phase (n=48) were 15.90±27.29, 10.41±16.74, 7.47±18.18, 8.19±15.70, 9.39±19.35, and 11.19±28.35 ng/m3 at Sri Vanathandavar Temple, Masjid Wadhi, Tadika Cahaya, Tadika Pasti, Monforth Youth Centre, and Maha Mariamman Temple, respectively, whereas the average concentration of particulate phase (n=35) was 0.24±0.23 ng/m3 at SK Sungai Udang. In the gaseous phase, the seasonal variations at sampling sites in Southwest Monsoon (June – September) observed the greatest level at 13.89±4.69 ng/m3 and the lowest during Intermonsoon 1 (October – November) at 8.22±5.26 ng/m3 . The diagnostic ratio showed that the primary contributors of PAHs in both phases are traffic emissions, petroleum and coal burning. The total Benzo(a)Pyrene equivalent carcinogenic (BaPeq) exposure was 5.27 - 22.02 ng/m3 in the volatile phase and 1.18 ng/m3 in the particulate aerosol phase. For carcinogenic risk, the incremental lifetime cancer risk (ILCR) in adults was higher compared to children and adolescents in both gaseous and particulate phases. The Hazard Quotient (HQ) for the adolescent in the gaseous phase (9.86E-03) was relatively higher compared to the particulate aerosol phase (1.01E-03).